Contemporary Developments in Child Protection Issues in Child Welfare - Nigel Parton (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Volume 2 "Issues in Child Welfare" is primarily concerned with how best to respond to maltreatment 'within' the family and hence has a range of papers which are much more concerned with the area of policy and practice more traditionally framed in terms of 'child welfare' and social work with children and families. It also includes a paper on how to respond to child maltreatment and neglect in a large hospital context.